Analysis of the Structural Behavior of the 6-Story the Pastoral Center of the Archdiocese of Pontianak to Earthquake Loads - Vian, Ryan Al; Herwani, Herwani; Elvira, Elvira (Jurnal Teknik Sipil, 2024)
This study analyzes the structural behavior of the 6-story Pastoral Center of the Archdiocese of Pontianak under earthquake loads, emphasizing its stability, safety, and performance in soft soil conditions. The analysis includes evaluating load combinations, response spectrum curves, stability coefficients, and P-Delta effects. Results indicate that the building's structural stability meets seismic standards, with load combinations effectively calculated and deviations between design and actual conditions remaining within allowable tolerances. The response spectrum curve highlights peak accelerations during short periods, corresponding to the region's soft soil characteristics. The P-Delta effect does not significantly impact stability, confirming that the structure performs well under seismic loads. Future research is recommended to optimize earthquake-resistant designs for buildings with six or more stories, focusing on innovative materials, advanced foundation systems, and real-time monitoring technologies. This study concludes that the Pastoral Center structure provides adequate safety and stability while offering pathways for improving structural resilience in seismic-prone areas.